Effects of Optimized Acupuncture and Moxibustion Treatment on Depressive Symptoms and Executive Functions in Patients With Post-Stroke Depression: Study Protocol for a Randomized Controlled Trial - Luo, Meng; Duan, Zhaoyuan; Song, Xiaolei; Liu, Chengmei; Li, Ruiqing; Su, Kaiqi; Bai, Yanjie; Wang, Xiaodan; Fu, Wenbin; Gao, Jing; Feng, Xiaodong (Frontiers in Neurology, 2022)
Background: Post-stroke depression (PSD), a common neuropsychiatric comorbidity after stroke, has a negative impact on the survivors’ functional recovery and quality of life. It lacks effective therapeutic drugs with good curative effects and few adverse reactions. Preliminary experiments have shown that the optimized acupuncture and moxibustion treatment including acupuncture, moxibustion and auricular intradermal acupuncture (OAMT) improved depressive symptoms and neurological deficits in PSD patients. However, the evidence for its effectiveness is still insufficient. Hence, we designed this study to evaluate the efficacy and safety of the OAMT on PSD, and to explore its possible mechanism from the perspective of executive function. Methods/design: This is a randomized controlled trial, which will comprise a total of 134 patients with PSD. Participants will be randomized into the intervention group and the control group at a 1:1 ratio. All treatments will be given 5 times per week for 4 weeks. The primary outcome is the severity of depression, which will be evaluated by the Hamilton Depression Scale-17 (HAMD-17) and the Beck Depression Rating Scale (BDI). Secondary outcomes are several neuropsychological tests, including the Stroop Color and Word Test (SCWT), the Trial Making Test (TMT), the Digit Symbol Substitution Test (DSST) and the Matrix reasoning test (MRT). All outcomes will be evaluated at baseline, week 4, week 8, week 12 and week 20. At the same time, fMRI will be used to measure the functional connectivity in the cognitive control network (CCN) at baseline and 4 weeks after intervention. Discussion: This study aims to provide high-quality evidence for the efficacy and safety of the OAMT for treating PSD. In addition, this trial will be the first trial to explore if the improvement condition of depression in the OAMT group is related to the improvement of executive function and the favorable changes in the structure.